Acute Diarrhea Duration Between Children With Probiotic Therapy And Without Probiotic Therapy At Gotong Royong Hospital - Dwiranti, Jasinda; Angelina, Zenia; Kusuma, P. Y. (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: Diarrhea is one of the leading causes of mortality and morbidity in childrenthroughout the world. Based on Basic Health Research data (Riskesdas), the highest diarrheaprevalence occurs in children aged 1-4. One of the supportive therapies given to children whohave acute diarrhea is probiotic therapy. Probiotic therapy in children with acute diarrhea canreduce the frequency and duration of diarrhea. Purpose: To analyze the differences in acute diarrhea duration between children withprobiotic therapy and without probiotic therapy, a case study in Gotong Royong Hospital. Method: An experimental study with Cohort approach. The sampling technique used in thisresearch was consecutive sampling. The procedure of this research was carried out bycollecting primary data, recording probiotic therapy given to the acute diarrhea children whocome to Gotong Royong Hospital at Surabaya and doing outpatient care, then continued withmonitoring to the patient's parents everyday to find out the duration of acute diarrhea in thechildren after probiotic therapy. This research used the Mann Whitney analysis test. Results: We found that there were significant differences between the duration of acutediarrhea in the children with probiotic therapy and the children without probiotic therapy witha value of p < 0,001 (p<0.05). The average duration of acute diarrhea in children withoutprobiotic therapy is 3.25 days. Meanwhile, the average duration of acute diarrhea in childrenwith probiotic therapy is 1.25 days. The average difference between children with andwithout probiotic therapy was two days. Conclusion: There is a difference in the duration of acute diarrhea in the children withprobiotic therapy and the children without probiotic therapy at Gotong Royong Hospital inSurabaya.Â